Parental and Successor Liability in EU Competition Law Infringements - Moisio, Lotta (fi=Turun yliopisto|en=University of Turku|, 2016)
Under EU competition law, parent companies may be held jointly and severally liable for the competition law infringements committed by their subsidiaries. The possibility of holding parent companies liable demonstrates a significant exception from the idea of separate legal entities. However, it is not the only deviation developed under EU competition law. In cases, where the legal entity responsible for the anti-competitive conduct has changed its form, liability can be attributed to the new operator, in particular, to its successor. The principles of legal certainty and legitimate expectations are issues that surround the doctrines of parental and successor liability. The aim of this thesis is to present a comprehensive comparative analysis of the parental and successor liability doctrines and to clarify the conditions under which it is possible to attribute liability for the infringements of EU competition law. The main purpose is therefore to demonstrate the problems related to the allocation of liability and to discuss whether these liability principles, established to assure the effective enforcement of the EU competition rules, are good solutions. The research methods used in this thesis are the legal dogmatic approach and the comparative law approach. The former enables the possibility of using the case law and legislation as a framework in which the difficulties concerning the application of parental and successor liability can be discussed while the latter ensures the comparison of the characteristics and judgments. The doctrines of parental and successor liability are both well established, but the application practice has caused several difficulties. These problems derive from, inter alia, the broadness and disjointed developed of the doctrines. There has been much recent case law dealing with these issues and having the potential to open up a considerable risk and to allocate strict liability for parent and successor companies.